2018
DOI: 10.1021/acs.nanolett.8b03983
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field-Induced Creation and Directional Motion of Domain Walls and Skyrmion Bubbles

Abstract: Magnetization dynamics driven by an electric field could provide long-term benefits to information technologies because of its ultralow power consumption. Meanwhile, the Dzyaloshinskii-Moriya interaction in interfacially asymmetric multilayers consisting of ferromagnetic and heavy-metal layers can stabilize topological spin textures, such as chiral domain walls, skyrmions, and skyrmion bubbles. These topological spin textures can be controlled by an electric field, and hold promise for building advanced spintr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 51 publications
0
74
0
Order By: Relevance
“…Moreover, Ma et al [45] reported that the electric field could tune the creation and motion direction of skyrmion bubbles at room temperature (Fig. 12b), which is of great significance to the ultralow-energy-consumption devices based on skyrmions.…”
Section: Electric-field Control Of Noncollinear Spin Structurementioning
confidence: 99%
“…Moreover, Ma et al [45] reported that the electric field could tune the creation and motion direction of skyrmion bubbles at room temperature (Fig. 12b), which is of great significance to the ultralow-energy-consumption devices based on skyrmions.…”
Section: Electric-field Control Of Noncollinear Spin Structurementioning
confidence: 99%
“…The generation of magnetic skyrmions has recently been demonstrated by applying magnetic fields 10 , spin-polarized currents 27,32 , local heating 33 , laser beams 34,35 and electric voltage 36,37 . Meanwhile, skyrmions can also be generated in geometrical constricted devices 6,[38][39][40][41][42] by applying electrical currents 43 .…”
Section: P a G E 3 | 18mentioning
confidence: 99%
“…Moreover, the use of EF scheme can avoid the unexpected displacement of skyrmions during the writing process 26 . These features are of great significance to practical applications and have thus promoted the usage of electric field instead of current to manipulate skyrmions 21,22,[26][27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite recognition of the potential for the EF manipulation of skyrmions, experimental realizations are limited 21,22,[26][27][28][29] , especially at room temperature [27][28][29] . Room-temperature EF-induced switching of skyrmions was first experimentally realized in the ferromagnet/oxide heterostructures, where the external electric field was directly applied at the ferromagnet/oxide interface to induce an interfacial charge re-distribution.…”
Section: Introductionmentioning
confidence: 99%